OPEN CIRCUIT HEAT EXCHANGER DYNAMICS DURING FLOW REDUCTION TRANSIENT IN THEIR SECONDARY LOOPS (Journal of Engineering, 2011)
An experimental and theoretical analysis was conducted for simulation of open circuit cross flow heatexchanger dynamics during flow reduction transient in their secondary loops. Finite differencemathematical model was prepared to cover the heat transfer mechanism between the hot water in theprimary circuit and the cold water in the secondary circuit during transient course. This model takes underconsideration the effect of water heat up in the secondary circuit due to step reduction of its flow on thephysical and thermal properties linked to the parameters that are used for calculation of heat transfercoefficients on both sides of their tubes. Computer program was prepared for calculation purposes whichcover all the variables that affect such type of transient mechanisms. The effect of the power density inthe primary circuit and the water flow reduction percentage on the average temperature build up of thewater in the primary circuit was investigated. The elapsed time required for the primary circuit averagetemperature to reach a steady state value was also calculated. These calculations were supported withexperimental measurements conducted on a standard cross flow heat exchanger apparatus. Theexperimental results were compared with the theoretical results for certain power density value atdifferent flow reduction percentages which show a reliable agreement. This relative agreement wasnecessary to consider the mathematical model with certain assurance for calculating transient parametersfor higher power densities that are out of apparatus ranges. The results proved that water averagetemperature build up in the primary circuit has sharp tendency when the percentage of flow reduction inthe secondary circuit reach 25% of its nominal values.